"Minor crimes" against wildlife: Small offenses, lasting impact, and a proposed solution. Issue 12 (17th December 2020) - Minton, Elizabeth A.; Sisneros‐Kidd, Abigail M.; Monz, Christopher
Abstract: Past research has examined why people engage in negative consumer behaviors, but research has not adequately examined what drives minor crimes against wildlife, which is important given their prevalence and impact on the welfare of wildlife. We address this need for research with two studies that examine minor crimes against wildlife in the context of wildlife jams (i.e., traffic jams caused by wildlife in and around roadways that obstruct the normal flow of traffic). Study 1 introduces a research methodology very new to the field of marketing by using participant observation and geospatial data to characterize actual behaviors of people during wildlife jam events in a national park setting. Study 2 begins with a pre‐test identifying the primary reasons for participation in wildlife jams before the main study tests a message‐based intervention strategy to reduce wildlife jams using five conditions (no message, standard message, attitudes‐based message, norms‐based message, control‐based message). Results reveal that a norms‐based message reduced intentions to participate in wildlife jams the most, while all messaging tactics were more effective than no message. Findings build on the theory of planned behavior, and suggestions for decreasing consumer harm to wildlife are discussed.